EFIR MOYLARINING TAVSIFI, ULARNING ANANAVIY OLINISH USULLARI - Avezov, H; Homitova, G. (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
In the chemical industry, it is important to carry out their targeted synthesis of essential oils, in this regard, as an aromatherapy agent in medicine, as an aromatizer for food products, as a flavoring agent in the perfumery and cosmetics industry, as a flavoring agent in household chemicals. special attention is paid to the issues of developing mechanisms that are highly effective in creating drugs that are highly effective in obtaining substances. Therefore, this article proposes solutions aimed at solving the problems of identifying plants rich in essential oils, extracting essential oils from their composition using various traditional and modern methods